Antimicrobial activity of rhodanine-3-acetic acid derivatives - Krátký, Martin; Vinšová, Jarmila; Stolaříková, Jiřina (Bioorganic & medicinal chemistry, 2017)
Twenty-four 2-(4-oxo-2-thioxothiazolidin-3-yl)acetic acid (rhodanine-3-acetic acid)-based amides, esters and 5-arylalkylidene derivatives were synthesized, characterized and evaluated as potential antimicrobial agents against a panel of bacteria, mycobacteria and fungi. All of the derivatives were active against mycobacteria. N-(4-Chlorophenyl)-2-[5-(2-hydroxybenzylidene)-4-oxo-2-thioxothiazolidin-3-yl]acetamide demonstrated the highest activity against Mycobacterium tuberculosis with minimum inhibitory concentrations (MIC) of 8-16μM. Non-tuberculous mycobacteria were the most susceptible to 2-[5-(2-hydroxybenzylidene)-4-oxo-2-thioxothiazolidin-3-yl]acetic acids (MIC values ⩾32μM). The highest antibacterial activity against Gram-positive bacteria including methicillin-resistant Staphylococcus aureus exhibited 4-(trifluoromethyl)phenyl 2-(4-oxo-2-thioxothiazolidin-3-yl)acetate (MIC⩾15.62μM). Several structure-activity relationships were identified. The activity against Gram-negative and fungal pathogens was marginal.
Keywords: Methicillin-Resistant Staphylococcus aureus; antiinfekční látky; Spectrophotometry, Infrared; Anti-Infective Agents; Antifungal activity; Proton Magnetic Resonance Spectroscopy; Condensation; Microbial Sensitivity Tests; Acetic Acid; In vitro activity; 2-(4-Oxo-2-thioxothiazolidin-3-yl)acetic acid; grampozitivní bakterie; rhodanin; Rhodanine; protonová magnetická rezonanční spektroskopie; methicilin rezistentní Staphylococcus aureus; magnetická rezonanční spektroskopie s uhlíkem 13C; Gram-Positive Bacteria; Carbon-13 Magnetic Resonance Spectroscopy; Amides; Esters; spektrofotometrie infračervená; mikrobiální testy citlivosti; Antimycobacterial activity; Candida; Antibacterial activity; kyselina octová